Pengaruh Pembelajaran Daring Selama Pandemi Covid-19 Terhadap Tingkat Pemahaman Peserta Didik Beragama Buddha Di Sekolah Menengah Pertama Kabupaten Semarang - Eka Ariyanti (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2021)
The aims of study are: (1) to know how much the influences of online learning during covid-19 pandemic on the level of Buddhist students’ understanding in Junior High Schools (SMP) Semarang Regency. (2) to explain the influences of online learning during covid-19 pandemic on the level of Buddhist students’ in Semarang Regency Junior High Schools (SMP). This research was a quantitative study through a correlation approach. It carried out in Semarang Regency Junior High Schools (SMP) in April-June 2021. The populations of this study were 125 students, while the samples were 60 students. Techniques of collection the data was use questionnaire. It was used to measure variable of online learninga and the level of students’ understanding. The questionnaire given has been through testing validity and reliability. The technique of analysis data was used simple linear regression analysis through SPSS 16 program. The results of this study showed that there is are influencess of online learning during covid-19 pandemic on the level of Buddhist students’ understanding in Junior High School (SMP) Semarang Regency in the amount of 0,641 and whwn viewed from R square obtained is 29%. The influencess of online learning has affects to the level of Buddhist students’ understanding in Junior High School (SMP) Semarang Regency is positive and signifikan value through the results of simple linear regression test show that the correlation coefficient 0.541 is positive.